2016
DOI: 10.1002/1873-3468.12464
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of wild‐type Trichoderma reesei Cel7A catalytic domain in open and closed states

Abstract: Trichoderma reesei Cel7A efficiently hydrolyses cellulose. We report here the crystallographic structures of the wild-type TrCel7A catalytic domain (CD) in an open state and, for the first time, in a closed state. Molecular dynamics (MD) simulations indicate that the loops along the CD tunnel move in concerted motions. Together, the crystallographic and MD data suggest that the CD cycles between the tense and relaxed forms that are characteristic of work producing enzymes. Analysis of the interactions formed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…[8] Such rigid modelsc an constructively be complemented with molecular dynamics (MD) simulations to obtain information on molecular motionso ver ap eriod of time. [9][10][11][12] Relaxation-matrixc alculations are useful for relating NMR spectroscopic data to structural models from for example, docking poses, crystal structures or molecular dynamics output. [13][14][15] This approach is often ak ey step for the generation of detailed solution-state models bearingi nformation on the dynamics in biomolecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Such rigid modelsc an constructively be complemented with molecular dynamics (MD) simulations to obtain information on molecular motionso ver ap eriod of time. [9][10][11][12] Relaxation-matrixc alculations are useful for relating NMR spectroscopic data to structural models from for example, docking poses, crystal structures or molecular dynamics output. [13][14][15] This approach is often ak ey step for the generation of detailed solution-state models bearingi nformation on the dynamics in biomolecular systems.…”
Section: Introductionmentioning
confidence: 99%
“…Product inhibition is a topical question in CBH catalysis. On the one hand cellobiose negatively affects the overall reaction rate and its inhibition should be alleviated by means of selection of CBHs from other sources or respective mutations of the downstream sites in HjCel7A . On the other, strong cellobiose affinity for downstream (expulsion) sites drives the processive hydrolysis by CBH and provides decrystallization free energy to overcome cellulose recalcitrance .…”
Section: Resultsmentioning
confidence: 99%
“…Stahlberg et al reported that divalent metal ions, as Ni 2+ , Co 2+ , Ca 2+ , Mn 2+ , and Mg 2+ , seem to be required by crystallization [24]. There are several CBHI structures containing the different ions, e.g., Sm 3+ and Gd 3+ , than divalent ones [30,31]. Before deciding on the swapped region for Co 2+ coordination, the crystal structures displaying more than 95% sequence similarity and also the high level of structural similarity within our reference structure (CBHI enzyme) are carefully examined.…”
Section: Construction Of Egi_swapped and Cloning Approachmentioning
confidence: 99%
“…Before deciding on the swapped region for Co 2+ coordination, the crystal structures displaying more than 95% sequence similarity and also the high level of structural similarity within our reference structure (CBHI enzyme) are carefully examined. Among 26 reported crystal structures, only 7 ones contain different metal ions than Co 2+ , e.g., Sm 3+ in PDB id: 4P1H, Gd 3+ in PDB id: 5TC9, and Ca 2+ in PDB id: 1CEL, 2CEL, 3CEL and 4CEL [30][31][32][33]. To make a true decision for swapping, we also perform the structural alignments between EGI (PDB id: 1EG1) with them.…”
Section: Construction Of Egi_swapped and Cloning Approachmentioning
confidence: 99%
See 1 more Smart Citation